Weed Control in Dicamba-Resistant Soybean with Glyphosate/Dicamba Applied at Various Doses and Timings - Nader Soltani; Christy Shropshire; Peter H. Sikkema (International Journal of Agronomy)
Seven field trials were completed over a three-year period (2016 to 2018) in southwestern Ontario, Canada, to assess weed control in conventional-till dicamba-resistant (DR) soybean with glyphosate/dicamba (2 : 1 ratio) applied postemergence (POST) at 3 doses (900, 1350, and 1800 g·ae·ha−1) and 3 application timings (up to 5, 15, and 25 cm weeds). There was minimal soybean injury (≤2%) from treatments evaluated. Glyphosate/dicamba applied at application timing of up to 5, 15, and 25 cm weeds, controlled Amaranthus spp. (pigweed spp.) 87–96, 94–99, and 99%; Ambrosia artemisiifolia (common ragweed) 93–99, 97–99, and 99–100%; Chenopodium album (lambsquarters) 89–99, 95–100, and 99–100%; Echinochloa crus-galli (barnyardgrass) 81–84, 94–96, and 96–97%; Setaria faberi (giant foxtail) 37–90, 77–98, and 99–100%; and Setaria viridis (green foxtail) 94–96, 99, and 99–100%, respectively. Additionally, glyphosate/dicamba applied POST at 900, 1350, and 1800 g·ae·ha−1 controlled Amaranthus spp. 90–97, 95–98, and 97–99%; A. artemisiifolia 95–98, 97–99, and 99–100%; C. album 92–99, 95–100, and 98–100%; E. crus-galli 84–88, 93-94, and 95-96%; S. faberi 74–95, 75–97, and 79–98%; and S. viridis 98, 98–99, and 98–100%, respectively. Weed interference reduced DR soybean yield as much as 51% compared to the highest yielding treatments. Results indicate that glyphosate/dicamba applied POST at the label doses can provide an adequate control of troublesome weeds in DR soybean. Weed control was generally most consistent when glyphosate/dicamba was applied at the highest registered dose in Ontario (1800 g·ae·ha−1) and when weeds were up to 25 cm tall.